2017
DOI: 10.5380/dma.v40i0.43655
|View full text |Cite
|
Sign up to set email alerts
|

Fitoterapia na Amazônia: a experiência do estado do Amapá-Brasil

Abstract: Artigo recebido em 25 de outubro de 2015, versão final aceita em 10 de janeiro de 2017. RESUMO:Este trabalho discute as perspectivas da utilização de plantas medicinais e fitoterápicos na Amazônia, a partir da experiência desenvolvida no Estado do Amapá, localizado na fronteira setentrional da Amazônia brasileira. A pesquisa utilizou os procedimentos metodológicos empregados pela REDESIST da Universidade Federal do Rio de Janeiro para o estudo de Arranjos Produtivos Locais, fazendo as adequações necessárias ao… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 1 publication
0
5
0
2
Order By: Relevance
“…The species with the highest levels of use agreement and frequency were Carapa guianensis, Pentaclethra macroloba, Dalbergia monetaria, Uncaria tomentosa, Otacanthus azureus, Virola surinamensis, Hura crepitans and Euterpe oleracea . In other studies, carried out in the Brazilian Amazon, the species Carapa guianensis, Pentaclethra macroloba, Uncaria tomentosa, and Virola surinamensis were also the most cited in terms of therapeutic use, demonstrating their regional value and the certainty that these plants may become targets in pharmacological research in the region [56, 57].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The species with the highest levels of use agreement and frequency were Carapa guianensis, Pentaclethra macroloba, Dalbergia monetaria, Uncaria tomentosa, Otacanthus azureus, Virola surinamensis, Hura crepitans and Euterpe oleracea . In other studies, carried out in the Brazilian Amazon, the species Carapa guianensis, Pentaclethra macroloba, Uncaria tomentosa, and Virola surinamensis were also the most cited in terms of therapeutic use, demonstrating their regional value and the certainty that these plants may become targets in pharmacological research in the region [56, 57].…”
Section: Resultsmentioning
confidence: 99%
“…It was observed that most of the plants used are related to diseases such as microbial infections (20.67%, 73 species), gastrointestinal disorders (13.31%, 47 species) and inflammations (11.61%, 41 species), emphasizing that 1 specie can be cited for several diseases (Table 2). Studies carried out in traditional communities in Brazil often point to several plant species for problems of the gastrointestinal system, including parasitic diseases and infections caused by microbial agents [57, 74, 75]. These results corroborate studies carried out in communities that do not have basic sanitation in developing countries alongside Latin America [38, 57, 76–79], and this ranking may therefore be related to economic conditions and regional habits as the riparian region studied does not present basic sanitation, and the community uses septic tanks and collects water directly from the river for their essential needs.…”
Section: Resultsmentioning
confidence: 99%
“…Besides the common use, that can confer "social validation" to these "old" services, as some of these records were published more than 30 years ago and because of it they should be considered strategic in governmental policies of primary and basic healthcare in the Amazon. This perspective can include policies of social inclusion (Filocreão et al 2017) and equalize health policies within the targeted territory (Pires et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This access can be facilitated through 'bonding social capital' and, especially, 'bridging social capital' as well as 'linking social capital', respectively. However, the system in question also has its downside, as it can lead to (strengthening) dependency of agroextrativistas -who make use of it (most of them at CCPT) -from these service providers (Filocreão, 2007;Silva, 2007). Still, trust systems among Brazil nut actors is pivotal for enabling the use of social capital and thus the potential access to market opportunities and resources.…”
Section: Mutual Dependency and Trust Relationshipsmentioning
confidence: 99%
“…Despite the well-known potential for Brazil nut extraction to help reconcile livelihood needs and forest conservation through its sustainable management (based on Peres et al, 2003;Filocreão, 2007;Scoles & Gribel, 2012), in many areas where extraction takes place (i.e. Amazon region in Brazil, Peru and Bolivia; Peres et al, 2003), there remains a disconnection between socioeconomic development of the Brazil nut value chain and environmental conservation, as in the Lower Amazon basin, state of Pará, Brazil.…”
Section: Introductionmentioning
confidence: 99%